Assessment of heritability and genetic efficiency in advanced sesame inbred lines - Hossein Zeinalzadeh-Tabrizi (Journal of Animal and Plant Sciences, 2024)
The estimation of heritability is critical in selecting the breeding strategy for various characteristics in agricultural plants. A randomized complete block design (RCBD) with four replications was used at Moghan Agricultural Research Station in Iran during the 2017-2018 crop years to evaluate heritability and genetic efficiency in 14 advanced sesame lines and the Oltan cultivar as a control variety. The number of days to flowering (DF), growth period (GP), plant height (PH), number of capsules per plant (CN), capsule length (CL), 1000-seed weight (SW), seed (SY), and oil yield (OY) were all measured during the experiment. Selected sesame lines were utilized to estimate genetic parameters, heritability, and genetic advance using the restricted maximum likelihood (REML)/best unbiased linear prediction (BLUP) method. The results revealed moderate GCV and PCV values for CN (13.58, 17.24), SY (14.45, 17.74), and OY (15.08, 18.15), whereas the other traits had lower values. Moderately high heritability in the broad sense with high GAM was found in CN, SY, and OY, while low heritability and low GAM were found for phenological traits, DF, and GP. It may be stated that the selection strategy used in sesame breeding lines in terms of CN with moderately high heritability in the broad sense and high GAM, as well as a strong positive correlation of CN with SY and OY, could reach maximum efficiency with which it provided the high-yielding genotypes that were needed for its breeding program.
Keywords: Correlation; Genetic advance; REML/BLUP; Selection; Yield